Gaya Bahasa Berita Media Online di Indonesia: Judul Menarik Tidak Harus Tidak Baku - Mariani Dewi (Bina Nusantara University, 2014)
Online media faces the challenge the urgency of news delivery, fierce competition in capturing audience attention, and changing of audience demography toward younger audience. So, media workers are required to use various means to attract Internet readers. One of the ways is using simpler and more popular language in delivering the news. This study tries to find out if it prompts online news media to undermine formal language because the use of popular words that are still not accepted by Indonesia's language authority and the type of nonformal language used. Research used quantitave approach to analyze the usage frequency of nonstandardized language by two major online media in Indonesia: detik.com and kompas.com, and case study to analyze the nonstandardized titles used. Study concludes that detik.com used considerably higher percentage of nonstandardized words compared to kompas.com. In one day, around 5% of the news titles published by www.detik.com contained one or more nonstandardized words; while less than 0.002% of kompas.com's news title used nonstandarized words. Judging from the popularity of kompas.com, it can be assumed that interesting and attractive titles can still be written without nonstandardized language. Furthermore, the nonstandardized words used were mixed from foreign languages, local dialects as well as slangs usually used by youth. This assumption will be used as hypotheses for further study.